Autochthonous white grape pomaces as bioactive source for functional jams. (25th November 2018) - Restuccia, Donatella; Giorgi, Gianluca; Gianfranco Spizzirri, Umile; Sciubba, Fabio; Capuani, Giorgio; Rago, Vittoria; Carullo, Gabriele; Aiello, Francesca
Summary: Seeds and skins from grape pomaces of Pecorello and Mantonico cv underwent extraction (ultrasound–assisted or maceration), in order to obtain added‐value ingredients for the production of a functional pear jam. The antioxidant features of the extracts were tested by in vitro colorimetric assays. Among seeds, Mantonico by maceration (MSC) showed the best results, as well as Mantonico by ultrasound‐assisted extraction (MBs) among skin extracts. The selected extracts were fully characterised by NMR and MS techniques, confirming the presence of many polyphenols, flavonoids and tannins among others. Pectin was then derivatised by the grafting procedure with the active molecules of MBs and MSC. The latter produced the best antioxidant polymer also without toxicity evaluated using Caco‐2 cells and was used for the jam preparation. The functional pear jam showed improved antioxidant performances in comparison with its non‐functional counterparts as well as its maintenance over time (15 days). Abstract : Pomaces of Calabrian white grapes were proved to be a suitable sources of antioxidant compounds. After extraction and characterization, a green conjugation with pectine was carried out to obtain a functional pear jam with improved antioxidant properties also over time.